English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-07-18 04:44:56 · 8 answers · asked by mishi khan 1 in Science & Mathematics Mathematics

8 answers

It's because x^a / x^a = 1
LHS = x^(a-a) = x^0 = RHS = 1

2007-07-18 05:35:26 · answer #1 · answered by Dr D 7 · 0 0

x^a/x^b = x^(a - b)
so x^a/x^a = 1 = x^(a -a) = x^0

2007-07-18 04:51:50 · answer #2 · answered by John V 6 · 0 0

x^4 / x = x^(4 - 1) = x³
x³ / x = x ^(3 - 1) = x²
x² / x = x^(2 - 1) = x^1
x / x = x^(1 - 1) = x^0
But x / x = 1
Thus x^0 = 1

2007-07-21 20:14:45 · answer #3 · answered by Como 7 · 0 0

I assume you`re familiar with the 2nd rule of indices,

p^c divided by p^d = p^c-d.

Consider p^7 divided by p^7, then by the second rule, this is

equal to p^0.

However, we know that any number divided by itself, say

17 divided by 17 = 1,so,. p^7 divided by p^7 = p^0 = 1

Hence any number raised to the power of zero is one.

2007-07-18 07:15:15 · answer #4 · answered by Twiggy 7 · 0 0

x^6/x^6 = 1
and
x^6/x^6 = x^0

=> x^0 =1

2007-07-18 04:52:35 · answer #5 · answered by harry m 6 · 0 1

given the formula:
(x^a) / (x^b) = x^(a-b)
and
C/C = 1 for any non-zero C.

Let C = x^a
then
C/C = (x^a) / (x^a)
1 = x^(a-a)
1 = x^0

2007-07-18 04:57:00 · answer #6 · answered by buoisang 4 · 0 0

If x not equal to zero, choose any m not equal to zero.

x^0 = x^(m-m) = (x^m)(x^-m) = (x^m)/(x^m) = 1

2007-07-18 04:50:39 · answer #7 · answered by fcas80 7 · 1 0

I just had college algebra. It sucked, I am sorry you are on your own on this one.

2007-07-18 04:48:12 · answer #8 · answered by l'il mama 5 · 0 4

fedest.com, questions and answers